Effects of transthyretin on thyroxine and β‐amyloid removal from cerebrospinal fluid in mice. (September 2016) - Chen, Ruoli; Chen, Carl P; Preston, Jane E
Summary: Transthyretin (TTR) is a binding protein for the thyroid hormone thyroxine (T4 ), retinol and β‐amyloid peptide. TTR aids the transfer of T4 from the blood to the cerebrospinal fluid (CSF), but also prevents T4 loss from the blood‐CSF barrier. It is, however, unclear whether TTR affects the clearance of β‐amyloid from the CSF. This study aimed to investigate roles of TTR in β‐amyloid and T4 efflux from the CSF. Eight‐week‐old 129sv male mice were anaesthetized and their lateral ventricles were cannulated. Mice were infused with artificial CSF containing 125 I‐T4 / 3 H‐mannitol, or 125 I‐Aβ40/ 3 H‐inulin, in the presence or absence of TTR. Mice were decapitated at 2, 4, 8, 16, 24 minutes after injection. The whole brain was then removed and divided into different regions. The radioactivities in the brain were determined by liquid scintillation counting. At baseline, the net uptake of 125 I‐T4 into the brain was significantly higher than that of  125 I‐Aβ40, and the half time for efflux was shorter ( 125 I‐T4, 5.16; 3 H‐mannitol, 7.44; 125 I‐Aβ40, 8.34; 3 H‐inulin, 10.78 minutes). The presence of TTR increased the half time for efflux of 125 I‐T4 efflux, and caused a noticeable increase in the uptake of 125 I‐T4 and 125 I‐Aβ40 in the choroid plexus, whilst uptakes of 3 H‐mannitol and 3 H‐inulin remained similar to control experiments. This study indicates that thyroxine and amyloid peptide effuse from the CSF using different transporters. TTR binds to thyroxine and amyloid peptide to prevent the loss of thyroxine from the brain and redistribute amyloid peptide to the choroid plexus.